DEVELOPMENT OF PENSION RIGHTS FOR MIGRANT WORKERS ON THE TERRITORY OF THE EURASIAN ECONOMIC UNION (EUROPEAN AND ASIAN LAW REVIEW, 2022)
The Treaty on the Eurasian Economic Union defined the establishment of a shared labor force market as one of the main goals of the integration association. Ensuring the freedom of movement for workers from EAEU member states is inextricably linked with exercising their right to pension benefits. The Agreement on Pension Benefits for the Working Population of EAEU Member States is based on the recognition of equal rights for workers, territorial equality, and export of pensions. As of the effective date of the Agreement, pension rights of the working population of EAEU member states shall be developed in full parity with the citizens of the state of employment. The Agreement establishes the types of pension contributions based on which the pension rights of the working population of EAEU member states are developed and the types of pension benefits these legal norms apply to. The paper includes a comparative analysis of legislations of EAEU member states the provisions of which define the development of pension rights of the working population of EAEU member states. In the course of work, the conditions for pension rights development have been analyzed, similarities and differences have been identified. The conducted research has shown that the pension systems of EAEU member states are in the process of being restructured. The stability of the pension systems is impacted by demographic, economic and migration issues. Under their influence, EAEU member states introduce structural changes to the pension systems, improve the rate policy, raise the retirement age and raise requirements for the length of employment.